1996
DOI: 10.1111/j.1600-0536.1996.tb02222.x
|View full text |Cite
|
Sign up to set email alerts
|

Statistical evaluation of the persistence of acquired hypersensitivity by standardized patch tests

Abstract: Numerous studies have focused attention on the influence of various biological and environmental factors on contact hypersensitivity. In order to evaluate the persistence and/or modification of allergic contact sensitivity to a number of common contact sensitizers, the same standardized patch tests were repeated on 174 subjects with contact sensitivity after a time lapse of 5 years (1987-1992). In 18.4% of the cases, 1 or more sensitivities were lost; 28.7% of the patients had a higher number of positive patch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 6 publications
1
7
0
Order By: Relevance
“…A retrospective analysis of our contact allergy database showed that, when positive patch test reactions were later retested, 66.8% remained positive, meaning that >30% became negative. This is in line with previous literature . As expected, the large majority (almost 85%) of these non‐persistent reactions were initially weak positive (+).…”
Section: Discussionsupporting
confidence: 93%
“…A retrospective analysis of our contact allergy database showed that, when positive patch test reactions were later retested, 66.8% remained positive, meaning that >30% became negative. This is in line with previous literature . As expected, the large majority (almost 85%) of these non‐persistent reactions were initially weak positive (+).…”
Section: Discussionsupporting
confidence: 93%
“…Contact allergy to >4000 substances has been described (17), and the allergy has been considered to persist throughout life (18). However, there are only a few modern studies addressing this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have documented the existence of allergic contact hypersensitivity for periods of up to 10 years after diagnosis. [123][124][125][126] Although the intensity of the allergy may wane with lack of exposure, it is lifelong and will recur under proper conditions. 28 Thus, although the disease ACD exists only when symptomatic, the underlying pathophysiology (eg, allergic contact hypersensitivity or delayed-type hypersensitivity) remains.…”
Section: Worker's Compensationmentioning
confidence: 99%